2009
DOI: 10.1590/s0036-46652009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of small mammal prevalence of Leishmania (Leishmania) mexicana in five foci of cutaneous leishmaniasis in the State of Campeche, Mexico

Abstract: sUMMaRyIn the Yucatan Peninsula of Mexico, 95% of the human cases of Cutaneous Leishmaniasis are caused by Leishmania (Leishmania) mexicana with an incidence rate of 5.08 per 100,000 inhabitants. Transmission is limited to the winter months (November to March). One study on wild rodents has incriminated Ototylomys phyllotis and Peromyscus yucatanicus as primary reservoirs of L. (L.) mexicana in the focus of La Libertad, Campeche. In the present study, the prevalence of both infection and disease caused by L. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
(39 reference statements)
1
35
1
Order By: Relevance
“…Parasite demonstration: Based on previous studies in which local signs of infection by L. (L.) mexicana were always located at the base of the tail 10,11,35,36 , smears were made from samples collected at the edge of the lesion (avoiding ulcerated and/or heavily crusted parts) or from the inoculation site in absence of local signs. Moreover, smears were made from the liver and spleen samples.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasite demonstration: Based on previous studies in which local signs of infection by L. (L.) mexicana were always located at the base of the tail 10,11,35,36 , smears were made from samples collected at the edge of the lesion (avoiding ulcerated and/or heavily crusted parts) or from the inoculation site in absence of local signs. Moreover, smears were made from the liver and spleen samples.…”
Section: Animalsmentioning
confidence: 99%
“…As described previously a criterion to incriminate a primary reservoir of Leishmania stated that the infection in a reservoir species should be relatively nonpathogenic, that is, the infection should not lower the survival possibility of the animal since it has to live until the next transmission season, which is more than seven months in the Peninsula. In other words, the immune system of the reservoir must react to the presence of the parasite in such a manner that while preventing irrevocable damage, the parasite evades sterilizing immunity 36 .…”
Section: This Is the First Study That Examines P Yucatanicus Clinicamentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, Van Wynsberghe et al [60] observed that in addition to high rates of infection (50% and 100% during 1997-1998 and 2001-2004, respectively), most animals were asymptomatic in certain areas of an important focus of cutaneous leishmaniasis in the state of Campeche (Table 4). …”
Section: (Marmosa) Mexicana (Mexican Mouse Opossum)mentioning
confidence: 99%
“…The first attempt to find leishmanial hosts close to the Yucatan Peninsula was carried out in Belize in the early 1960s [29][30][31]. However, the south of Belize has to be considered as a different endemic area of the disease since this area is not part of the Biotic Province of the Peninsula of Yucatán [32] [18,33,34]. Thus, many small terrestrial mammals of the Peninsula seemed to be able to harbour the parasite.…”
Section: Reservoirsmentioning
confidence: 99%